2023
DOI: 10.1177/23259671231154921
|View full text |Cite
|
Sign up to set email alerts
|

Survivorship, Outcomes, and Risk Factors for Conversion to Total Hip Arthroplasty After Revision Hip Arthroscopic Surgery in Obese Patients: Results at a Minimum 5-Year Follow-up

Abstract: Background: There is a paucity of literature reporting outcomes after revision hip arthroscopic surgery in obese patients. Purpose: To report the minimum 5-year survivorship, patient-reported outcomes (PROs), clinical benefit, and risk factors for conversion to total hip arthroplasty (THA) in obese patients after revision hip arthroscopic surgery. Study Design: Case series; Level of evidence, 4. Methods: Data were prospectively collected and retrospectively reviewed for patients who underwent revision hip arth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Obesity was proven to be associated with a longer time to achieve PASS, 55 and Parvaresh et al 49 established that the obese population was 14.1 times less likely to achieve the PASS after primary arthroscopic FAIS surgery. In the revision hip arthroscopy setting, Maldonado et al 35 reported that 25% of patients with a BMI 30 will require a conversion to total hip arthroplasty at a minimum 5-year follow-up, and every additional year of age at the time of revision increased this by 29.7%.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity was proven to be associated with a longer time to achieve PASS, 55 and Parvaresh et al 49 established that the obese population was 14.1 times less likely to achieve the PASS after primary arthroscopic FAIS surgery. In the revision hip arthroscopy setting, Maldonado et al 35 reported that 25% of patients with a BMI 30 will require a conversion to total hip arthroplasty at a minimum 5-year follow-up, and every additional year of age at the time of revision increased this by 29.7%.…”
Section: Discussionmentioning
confidence: 99%